Students’ perceptions toward teaching materials for the Listening and Speaking for General Purposes subject - Hustarna, Hustarna; Arif, Nely; Habizar, Habizar (Universitas Islam Sultan Agung, 2025)
Teaching materials are crucial in education. They are tools for teachers to facilitate students to learn and improve the interaction of a teacher and students. Teaching materials should fulfill some criteria. One of them is the suitability of the materials to students' needs and interests. This study aims to explore students' perceptions toward teaching materials for the subject of Listening and Speaking for General Purposes. The study employs a mixed method. A questionnaire and an interview were used to gather the comprehensive data. The data from the questionnaire were analyzed using a statistical calculation, while the interview data were analyzed using thematic analysis. The teaching materials were provided by three lecturers from three different classes. The results showed that teaching materials used by D1 and D2 were considered good and beneficial for students, while the one used by D3 was perceived as inappropriate and did not help students improve their listening and speaking skills. Finally, this study recommends improving the teaching materials to meet students' needs and interests.